2022
DOI: 10.1002/jmv.27687
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and molecular characterization of human pegivirus‐1 (HPgV‐1) viremia in healthy volunteer blood donors from Northern Portugal

Abstract: Human pegivirus-1 (HPgV-1) is a member of the Flaviviridae family and the Pegivirus genus. Despite having been discovered 25 years ago, there is still much to know regarding HPgV-1 clinical impact, as this virus is currently not associated with any pathology. Yet, HPgV-1 prevalence and molecular characterization are still unknown in many countries, including Portugal. To fill in this knowledge gap, this study aimed to determine the occurrence and molecular characterization of HPgV-1 in a group of healthy blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Genotype 2 is a prevalent genotype of HPgV-1, being the most disseminated in Europe and the USA [ 29 , 30 , 31 ]. It is particularly detected among individuals who inject drugs [ 10 , 32 , 33 ]. Studies performed in Brazil show that in this Latin American country, genotype 2 is dominant [ 9 , 31 , 34 ]; this includes the state of São Paulo [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype 2 is a prevalent genotype of HPgV-1, being the most disseminated in Europe and the USA [ 29 , 30 , 31 ]. It is particularly detected among individuals who inject drugs [ 10 , 32 , 33 ]. Studies performed in Brazil show that in this Latin American country, genotype 2 is dominant [ 9 , 31 , 34 ]; this includes the state of São Paulo [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that it was initially detected in samples obtained from patients with acute hepatitis, it was supposed that HPgV-1 is a causative agent of acute hepatic conditions [ 8 ]. However, more detailed studies demonstrated that it has no significant pathologic impact and is widely distributed throughout the world, including in healthy subjects who donate blood [ 9 , 10 ]. Additionally, it was proposed that HPgV-1 positivity in HIV-infected patients and in patients who have undergone hematopoietic transplantation might exert a positive impact on immune reconstitution [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis G virus (HGV), also known as Human pegivirus (HPgV-1) or GB virus C (GBV-C), is a single-stranded ribonucleic acid (RNA) virus that is related to hepatitis C virus (HCV) [1,2]. It shares some genetic similarities with HCV and is found in patients with chronic liver disease [3,4]. However, unlike other hepatitis viruses, its role in hepatitis disease is still unclear [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…HGV causes no noticeable symptoms or signs of liver disease [3,5]. However, in some cases of chronic or long-lasting HGV infection, its presence in the bloodstream (viremia) has been documented [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation